Raṅganāthī Yogavāsishṭha : prākrta ovībaddha grantha subodha ṭīpā āṇi prastāvanā ỹāsaha - Raṅganātha, Swami, 1609-1684 (Induprakāśa, 1908)
Verse rendering of the abridged version of Yogavāsiṣṭharāmāyaṇa, early Vedantic approach in Hindu philosophy.